Śrīrāmakrshṇa Kathāmrta o lokasaṃskrti - Bandyopādhyāẏa, Subhāsha (Jaẏadīpa Pābalikeśanas, 1983)
Study on the elements of folk culture and idiom in Śrīśrī Rāmakrsaṇakathāmrta, collected teachings of Ramakrishna, 1836-1886, Hindu religious leader.